El parámetro de los compuestos en la adquisición del español como lengua extranjera considerando el tipo de lengua materna y el contexto de aprendizaje - Trias, Marta; Villanueva, Ana María (Colombian Applied Linguistics Journal, 2013)
The present article is part of a research project on the Compounding Parameter (Snyder 1995, 1996, 2001) within the framework of Universal Grammar. According to the typology established by Snyder (1995, 1996, 2001), languages are categorized by the presence or absence of productive [NN] compounds and complex predicates. A grammatical judgment test and a multiple choice test were used to observe the answers of students of Spanish as a foreign language, grouped according to the type of mother tongue and learning context, instructional (US) or instructional + natural (Venezuela). Results indicate that the combination of natural + instructional learning context promotes the learning of some of the structures of the parameter studied in the article; there is also the tendency of the production of left headed [NdeN] and [NN].